2006
DOI: 10.1007/s10798-005-5052-2
|View full text |Cite
|
Sign up to set email alerts
|

The Shifting Tides of Academe: Oscillation between Hand and Computer in Architectural Education

Abstract: There is a current vacillation in choosing hand or computer for design presentation in academia. Although the computer emerged as very powerful alternative presentation medium, it could not sweep away the hand totally. Believing that this vacillation cannot only be due to the positive and negative aspects of both media, we worked with a group of students in a design curriculum to observe the factors that affect their choice of medium for presenting design ideas. The students were required to use both media for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 14 publications
1
14
0
2
Order By: Relevance
“…The authors of this study come close to telling the whole story -not just the propaganda -of using ICT for the professional education of architects, and as such it is invaluable. Apili & Basa (2006) offer even more surprising -and perhaps disturbing -empirical findings about the use of computers for architectural education. In a study of second-year design students these authors found that there was a strong oscillation in preference between using the hand and using the computer for drawing designs.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of this study come close to telling the whole story -not just the propaganda -of using ICT for the professional education of architects, and as such it is invaluable. Apili & Basa (2006) offer even more surprising -and perhaps disturbing -empirical findings about the use of computers for architectural education. In a study of second-year design students these authors found that there was a strong oscillation in preference between using the hand and using the computer for drawing designs.…”
Section: Discussionmentioning
confidence: 99%
“…A manual–digital hybrid approach, involving ideation on paper and final drawings on the computer, may be problematic in that the design process is interrupted when the designer shifts from one medium to the other (Meneely & Danko, ). We propose that more current research is needed; the rate at which technologies evolve leaves a clear gap between what has been learned about the digital process over the past 10 years—see examples in Bilda, ; Bilda & Demirkan, ; Dickinson, Yu, Zeng, & Antunes, ; Maldonado, Lee, & Klemmer, ; Şenyapili & Basa, ; Dorta, Pérez, & Lesage, —and what is most current and relevant to interior design educators today. The present study will explore the efficacy of four contemporary digital drawing tools—mouse, iPad, Wacom Cintiq and Bamboo—when measured by interior design students' perception of technical and esthetic quality outcomes.…”
Section: Design Process As Affordance‐based Interactionmentioning
confidence: 99%
“…In design studios, the students represent their design ideas through sketches and discuss their design solutions with their instructors. Sketches as the external representations provide a link between the actual world and the mental world of the designer (Demirkan 2005;Senyapili and Basa 2006). Positive or negative critiques of the instructors on the design representations enable students to observe and assess their design projects.…”
Section: Content Of Critiques In Design Processmentioning
confidence: 99%